Resicore and Glyphosate Application Timings in Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments in irrigated corn. All treatments provided excellent, season-long control of kochia, Russian thistle, Palmer amaranth and green foxtail. Herbicide-treated corn yielded 219 to 235 bu/a, which was 86 to 102 bu/a more than nontreated corn; however, no differences in yield occurred among herbicide treatments.
Keywords: Preplant; sequential applications